The Use of Lemongrass in Tea Bag Production Towards the First Ecotourism Village in North Sulawesi Province - Herry Frits Pinatik; Rine Kaunang; Stella Deiby Umboh; Mukhlis (Unram Journal of Community Service, 2025)
The use of lemongrass (Cymbopogon citratus) in the production of tea bags in the first ecotourism village in North Sulawesi Province is an innovative step to boost the local economy and support environmental sustainability. This study aims to explore the quality of lemongrass tea bags, community acceptance, economic impact, and environmental aspects of this initiative. The results show that lemongrass tea bags have an aroma and taste that is liked by 85% of respondents, as well as a high antioxidant content. The local community showed great enthusiasm, with 70% of farmers interested in producing tea bags as an additional source of income. Farmers' income increased by about 30% within six months after training, and this product also supports environmental sustainability by reducing pesticide use. Effective marketing strategies and promotion through social media and local festivals are proposed to increase product visibility. This initiative not only provides economic benefits but also strengthens social solidarity and community pride. Community towards   their local. Thus, the use of lemongrass in the manufacture of tea bags has the potential to become an icon of ecotourism villages that support economic growth and environmental sustainability in North Sulawesi.